Implementation of Legal Protection in Preventing Brand Coffering in The SME’s Sector - eni dasuki (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Small and Medium Enterprises (SME’s) are highly susceptible to the risks posed by counterfeiting and unauthorized utilization of brands, akin to their larger counterparts. Primarily, the challenges encountered, particularly by SME’s, stem from a lack of comprehensive comprehension regarding the essence of a brand and the repercussions of counterfeiting. Brand infringement typically transpires in environments of intense business rivalry within the product domain. The primary objective of this study is to explore the legal safeguards available for brands and strategies aimed at enhancing brand resilience. The employed methodology in this study encompasses normative juridical inquiry and interviews conducted with four SME’s. The findings underscore that legal protection may be actualized through (1) fostering self-awareness among SMEs, (2) furnishing them with appropriate counsel and direction, and (3) facilitating the registration process, whether individually or collectively.